Dowland, Lachrimae (1604) - Holman, Peter 1946- (Cambridge University Press, 1999)
Dowland's Lachrimae (1604) is perhaps the greatest but most enigmatic publication of instrumental music from before the eighteenth century. This new handbook, the first detailed study of the collection, investigates its publication history, its instrumentation, its place in the history of Renaissance dance music, and its reception history. Two extended chapters examine the twenty-one pieces in the collection in detail, discussing the complex internal relationships between the cycle of seven 'Lachrimae' pavans, the relationships between them and other pieces inside and outside the collection, and possible connections between the Latin titles of the seven pavans and Elizabethan conceptions of melancholy. The extraordinarily multi-faceted nature of the collection also leads the author to illuminate questions of patronage, the ordering and format of the collection, pitch and transposition, tonality and modality, and even numerology
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Dowland, John / 1563?-1626 / Lachrimae; Dowland, John -- 1562-1626 -- Lachrimae -- Consortmusik